Подождите немного. Документ загружается.
V V ¯ϕ
F
∆[...]
¯ϕ
i
x
x =
i
− i
r
= x
ξ, 0 ξ 1,
ξ x
ϕ =
ρ
x
ρ
+(ρ
− ρ
)x
¯ϕ =
1
0
ϕ (ξ)dξ =
ρ
ρ
− ρ
1 −
ρ
(ρ
− ρ
)x
ln
1+
ρ
− ρ
ρ
x
.
d
dt
(ρ
(1 − ¯ϕ )V + ρ
¯ϕ V )=D − D ;
d
dt
(ρ
i
(1 − ¯ϕ )V + ρ
i
¯ϕ V + G c ϑ
)=Q + D i
− (i
+ rx )D ,
D D G
D
e
32
(p ,x )
dp
dt
+ e
33
(p ,x )
dx
dt
= Q − rx
D ,
e
32
(p ,x )=
ρ
∂i
∂p
−x r
∂ρ
∂p
(1−¯ϕ
)V +
(1−x )r
∂ρ
∂p
+ρ
∂i
∂p
¯ϕ
V +
+(ρ
+(ρ
− ρ
)x )rV
∂ ¯ϕ
∂p
+ G c
∂ϑ
∂p
;
e
33
(p ,x )=(ρ
+(ρ
− ρ
)x )rV
∂ ¯ϕ
∂x
.
D
k
2
D
2
ρ
f
2
=(ρ
− ρ
)¯ϕ gH
D =
2ρ
(ρ
− ρ
)¯ϕ gV f
k
,
f k
g
H = V /f
e
11
(p )
dV
dt
+ e
12
(p ,V
)
dp
dt
=D
− D −D
;
e
21
(p )
dV
dt
+ e
22
(p ,V
)
dp
dt
=D
i − D i
− D
i
+ Q;
e
32
(p ,x )
dp
dt
+ e
33
(p ,x )
dx
dt
=Q − rx
D (p ,x );
∆h =∆
V
− V − (1 − ¯ϕ )V
F
.
dh
dt
=
1
F
dV
dt
+ V
∂ ¯ϕ
∂p
dp
dt
+ V
∂ ¯ϕ
∂x
dx
dt
,
˜e
12
−e
11
V
∂ ¯ϕ
∂p
dp
dt
−e
11
V
∂ ¯ϕ
∂x
dx
dt
+e
11
F
d∆h
dt
=D
−D −D
;
˜e
22
−e
21
V
∂ ¯ϕ
∂p
dp
dt
−e
21
V
∂ ¯ϕ
∂x
dx
dt
+e
21
F
d∆h
dt
=D
i −D i
−D
i
+Q;
e
32
(p ,x )
dp
dt
+ e
33
(p ,x )
dx
dt
=Q − rx
D (p ,x ),
˜e
12
˜e
22
e
12
e
22
V
(V
)
0
+ V +(1− ¯ϕ )V + F ∆h (V
)
0
V
d¯ρ
dt
=
˜
D
+ D − D ,
V ¯ρ
˜
D
D
D
D
p −p = ξ
(
˜
D
)
2
¯ρ
;
¯ρ =0, 5(ρ
(p ) − ρ (p ,ϑ )),
ξ p ϑ
ρ (p, ϑ)
p − p
ϑ = ϑ
0
p
p
1
ρ
(p ) ρ (p
1
) ρ (p )
V
∂ρ (p
1
,ϑ
1
= idem)
∂p
1
dp
1
dt
=
˜
D
+ D − D .
p − p
1
= ξ
I
(
˜
D
)
2
¯ρ
I
;
p
1
− p = ξ
II
D
2
¯ρ
II
,
¯ρ
I
¯ρ
II
¯ρ
I
=¯ρ
I
(p ,p ); ¯ρ
II
=¯ρ
II
(p ,p ).
¯ρ
V
∂ρ (p ,ϑ
0
)
∂p
dp
dt
=
˜
D
+ D − D ;
˜
D
(p ,p )=
˜
D
0
ρ (p ,ϑ
0
)
ρ (p
0
,ϑ
0
)
(p
− p )
(p
0
− p
0
)
.
D (p ,µ )=
D
0
µ
0
p
0
p µ .
J
dω
dt
= M
− M ,
ds
i
dt
= k
i
ω
i
;
T
i
dω
i
dt
= −ω
i
+ U
i
,
V
j
dρ
j
dt
= D
j−1
− D
j
− D
j
.
J ω M
M s
i
ω
i
i
U
i
i
T
i
i k
i
i s
i
V
j
ρ
j
j D
j−1
D
j
D
j
j j +1
M =
N
j=1
M
j
.
M
j
∆H
j
η
j
D
j
M
j
=
∆H
j
D
j
η
j
ω
.
p
ρ
γ
=const p ρ γ
j
ρ
j
= ρ
0
p
j
p
0
1
γ
,
p
0
ρ
0
D
()
D
()
=
2γ
γ − 1
⎛
⎝
p
p
0
2
γ
−
p
p
0
γ+1
γ
⎞
⎠
p
0
√
RT
0
F,
R
F
D
()
= B
0
p
0
√
RT
0
F,
B
0
B
0
=
χ
1 − ε
−ε
2
+2ε ε+1−2ε =
χ
1 − ε
(1−ε )
2
−(ε −ε)
2
ε =
p
p
0
ε χ
ε =
2
γ +1
γ
γ−1
,χ=
2
γ +1
γ+1
γ−1
γ.
ε ≈ 0, 546 χ ≈ 0, 667
D
()
= D
()
p
0
p
0
T
0
T
0
−ε
2
+1, 09ε − 0.09
−ε
2
+1, 09ε − 0.09
F
F
,
ε = ε
D
()
= D
()
p
0
p
0
T
0
T
0
F
F
.
D
()
= D
()
p
0
p
0
F
F
.
Jω
dω
dt
=∆H · D
(p ) − N ;
V
ρ
0
γp
0
dp
dt
=
p
p
0
m
(D (p ,p ,s) − D (p )) ;
ds
dt
= k
ω ;
T
dω
dt
= −ω
+ U ;
D
= D
0
B
0
(p /p )
B
0
(p
0
/p
0
)
p
p
0
F
F
0
; D = D
0
p
p
0
.
p B
0
m
γ
m =
γ − 1
γ
.
γ ≈ 1, 3 ⇒ m ≈
3
13
F (s)
F = F
s +
1
4
sin(πs)
.
T
1
=
V
ρ
0
γD
0
; T
2
=
Jω
2
0
N
0
,
T
2
N
0
ω
2
0
ω
dω
dt
=∆H · D
(p ) − N ;
T
1
D
0
p
0
dp
dt
=
p
p
0
m
(D (p ,p ,s) − D (p )) ,
T
1
T
2
•
•
•
•
•
•
h h
W
D
(s) W
D
(s) W
h
(s)
W (s) ε
h
ε
D
D D
λ
D
λ
h
y
q
u
M
k
T
= max M M .